PECULIARITIES OF ENT-DAMAGE IN CHILDREN WITH CYSTIC FIBROSIS - I.V. Martynova; E.P. Karpova; N.I. Kapranov ("Paediatrician" Publishers LLC, 2011)
Traditional approach to cystic fibrosis patients treatment doesn't involve upper respiratory tract assessment, though abnormal changes - consequences of the cystic fibrosis transmembrane conductivity regulator gene mutation- do affect nasal and paranasal mucosa to the same extent. Approximately half of cystic fibrosis patients suffer from chronic rhinosinusitis and/or nasal polyposis that worsens the clinical course of already severe disease. Chronic hyperplasia in paranasal cavities can be quite extensive, recurrent and can lead to destruction of osseous walls of the cavity and of nasal septum. Thus increasing the amount of hospital admissions and and their duration. Low awareness of ENT-specialists working in polyclinics and in hospitals of ENT-pathology in cystic fibrosis patients leads to belated diagnostics, excessive manipulations, ineffective treatment, including surgery. All these lays grounds to implication of the early screening diagnostic program and development of proper treatment methods of ENT-complications of cystic fibrosis - therapeutic as well as surgical, with strict specification of indications and contraindications. Key words: cystic fibrosis, chronic rhino sinusitis, nasal polyposis. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (5): 49-53.)